Improving Students’ Listening Skill in Procedure Text through Playing Video at the Eleventh Grade of Senior High School - Kristof Martin Efori Telaumbanua (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
By listening, people are able to receive message accurately in communication process. 20123 Curriculum at the Eleventh grade of SMAN 1 Tuhemberua expects the students to catch contextually meaning of procedural text. There were some research problems namely: the students are unable to understand the meaning of the sentence convey, the students are quickly forgetting meaning of the sentence what is heard, the students are unable to understand the generic structure of procedure text, the students are unable to use the connective sentence of procedure text. The purpose of this research is to improve listening skill in English lessons. In improving the students’ listening skill, the research used playing video and applied Classroom Action Research. The research has been conducted in two cycles, which each cycle consisted of two meetings, there were four steps in conducting the research, namely Planning, Action, Observation, and Reflection. In Cycle 1 there were 10 students (50%) got score among 40-59 got level of less, 8 students (40%) got score among 60-74 got level of enough, and 2 students got score 75-84got level of good, while in cycle II there were 10 students got score among 75-84 got level of good, 10 students (50 %) got score among 85-100 got level of very good. Based on the result of the research, it can be concluded that playing video improves the students’ listening skill. Finally, the researcher writes some suggestion; a) The teacher are encourage to apply playing video in procedure text, because it has a better effect on students’ ability and motivate students to learn more fun teaching-learning activities, b) The teacher needs to explain the purpose of the technique to get a good result, c) In teaching listening through playing video, the teacher should select the listening material for the students to make them interest and active in the teaching-learning process.